Sõja- ja kodurinde suhted I maailmasõjas osalenud eesti sõdurite kirjades ja mälestustes [Relations between fighting front and home front in letters and memoirs of Estonian WWI soldiers] - Eglit, Liisi (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2012)
The aim of this article is to take a glance at the WW I experience of Estonian soldiers and society. More precisely, I use the concepts of fighting front and home front in order to analyse the relationship between Estonian soldiers and society during and shortly after the war. When analysing the relations during the war, I characterize the communication between the two fronts, trying to explain the relationship and the transformations it went through by using the images of both fronts in the soldiers’ eyes. Concerning the post-war period, I portray the soldiers’ self-image as well as the image of the society and analyse why these images were different from those characteristic to the wartime period.(Longer version of the current abstract is included in the article, starting from p 85.)